Pemanfaatan Teknologi Digital Bagi Efektivitas Penginjilan dan Pemuridan Generasi- Z - Sasono, Dimas; Boiliu, Esti Regina (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
The development of digital technology has changed the way humans communicate and interact, including in the life of faith and church ministry. Generation Z, who grew up in the digital world, has a different way of interacting with previous generations, more accustomed to fast, visual, and interactive information. This poses a challenge for the church to convey the gospel in a relevant manner without losing the essence of Christian teachings. This research aims to analyse effective evangelism and discipleship strategies for Generation Z through digital technology, using a qualitative approach and literature study. The results show that social media, streaming platforms, digital storytelling, and Christian influencer engagement can increase the effectiveness of church ministry. Social media also serves as a flexible discipleship space for Generation Z. However, digitalisation carries the risk of misinformation, disinformation, and reduced deep spiritual engagement. Therefore, it is important to integrate Christian values in the use of technology. In conclusion, digital technology offers great opportunities for evangelism and discipleship, but churches need to be wise in managing the risks involved. The novelty of this research lies in the use of digital technology to create interactive spaces and spiritual communities for Generation Z.